Analysis Of Gastrointestinal Malignancy: A Five Years Study - Patel , Mandakini M; Gamit , Bhavna; Patel , Prashant R (National Journal of Community Medicine, 2012)
With addition of western life style GI malignancy is increasing in developing country. Recent studies have indicated increasing incidence. Our study was five year analysis of Gastrointestinal Malignancies diagnosed in the Department of Pathology, Government Medical Collage Surat. This study includes 244 cases of gastrointestinal tract malignancies. Incidence of gastrointestinal malignancy was gradually increased from 2006 to 2010. Most common age group affected was 41-50 years (64 cases, 26.22%) followed by age group of 51-60 year (58 cases, 23.77%). Most common malignancy came across was esophageal carcinoma (38.93%) followed by colorectal carcinoma(32.79%) and carcinoma of stomach(16.80%). Microscopically, adenocarcinoma was the commonest malignancy (45.90%), followed by Squamous cell carcinoma (33.60%).